“Por que a lei não ‘pega’?”: um estudo sobre os mecanismos dificultadores à adoção e à difusão de práticas da lei de acesso à informação - Marcelino, Carolina Wünsch (2017)
The Law on Access to Information (LAI) is a regulatory landmark, which aims to bring freedom and disclosure to public information. However, five years after its promulgation in Brazil, regulatory agencies outline lack of compliance in many cities of Paraná State. Based on the city of Londrina, where many socio political facts took place in the last eight years, this research investigates which are and how operate mechanisms that hinders practices’ adoption and diffusion. A socio-legal study is undertaken, in order to emphasize social construction of the Law according to Legal and Organizational Institutionalism, under a linguistic approach. Focusing on practices and meanings, as well as in the way they are shared, this empirical research intends to emphasize the constitutive relations between Law, organizations and society, in its shades. Legal subjection to social and cultural aspects is reinforced, shaking static and purely arithmetical notions of what effectiveness and legal validity are. In emphasizing intersubjectivity, the importance of language is expanded, either by the condition of the Law as an open text, or by the need for intertwining between legal text and other texts and speeches, so that one can understand the law-in-practice and the law-in-thecontext. The importance of language is further materialized by the methods choice for the study: an interpretative discourse analysis, elaborated in accordance to Putnam and Fairhurst (2001) and Maguire and Hardy (2009). We used primary data – obtained through eight semi-structured interviews – and also secondary data – from documental analysis. By applying such method, textual and discursive elements (and their intertextualities) allowed the evaluation of lexical, grammatical and semantic elements, which evidenced the relation between the discursive activity and the practice. We also enumerate textual elements in order to differentiate and compare technical/legal language from popular/ordinary language, and the translation process underpinning them. Results indicate ten (10) mechanisms that impede legal compliance, classified in structural dimensions (2 mechanisms), discursive (5 mechanisms) and hybrid (3 mechanisms). In the structural dimension, we discuss the limitations imposed by the size of cities, and the need to broaden public agents’ training. In the discursive dimension, we list the adoption of ceremonial practices, the urge to convert technical/legal data into ordinary language, the influence of sensemaking on compliance and enforcement, the looseness of enforcement actions, and deficiencies in practices diffusion. Finally, in the hybrid dimension, we present decoupling and its roots in the internal information management, the cultural process of understanding the citizen as the owner of public information, and the high dependence of the Law on its regulation act. These aspects will converge to the contention that there is a gap between the ideal proposed by the law formalism (law-in-books) and the social realism (law-in-practice).